PENINGKATAN KEMAMPUAN MENULIS KALIMAT BAHASA INGGRIS MENGGUNAKAN MEDIA GAMBAR PADA KELAS BAHASA INGGRIS 2 MAHASISWA PGSD ANGKATAN 2015 UNHASY TEBUIRENG - Fajarina, Maskhurin (Discovery, 2018)
English for non-English department is important too. Some students have difficulties in applying their English in some skills, speaking, listening, reading, and writing. Writing an English sentence in needed by every students. But sometimes they feel difficult to get an idea and use the vocabularies. The researcher wanted to conduct the research related to the student’s difficulties in writing an English sentence. The problems of the research are how to conduct the student’s ability in writing an English sentence using picture and how the treatment can improve the student’s ability in writing an English sentence. The procedure of the research are planning, implementing, observing, and reflecting. The researcher conducted the research in two cycles; each cycle consisted of two meetings. The researcher used some instruments; those are scoring rubric of student’s written test and rubric of observing the class (non-test). The research used score 1-3. Before giving the treatment, the researcher conducted pre-test to empower the basic of student’s ability The result shows that in cycle I the score mean is 1,77 and in cycle II is 2,58. There is improving ability of writing an English sentence and the condition of the class. Keywords: pictures, ability of writing an English sentence,